2004
DOI: 10.1194/jlr.m300278-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

ATP binding cassette transporter G5 and G8 genotypes and plasma lipoprotein levels before and after treatment with atorvastatin

Abstract: The mechanisms responsible for interindividual variation in response to statin therapy remain uncertain. It has been shown that hepatic cholesterol synthesis is associated with ATP binding cassette transporter G5 and G8 (ABCG5/8) activities. To test the hypothesis that genetic variation in ABCG5/8 might influence the plasma lipid response to statin therapy, we examined five nonsynonymous polymorphisms at the ABCG5/8 loci (Q604E, D19H, Y54C, T400K, and A632V) in 338 hypercholesterolemic patients treated with 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
5
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 21 publications
4
78
5
2
Order By: Relevance
“…These results clearly demonstrated that the D19H polymorphism, even though it was rare, significantly contributed to an independent genetic risk of developing high total cholesterol and LDL-C levels. As reports have shown previously, this points to the fact that subjects with D19H/19H (GC or CC) variants are disposed to having a lower cholesterol absorption efficiency Hubáček et al 2004;Kajinami et al 2004aKajinami et al , 2004b. However, the cholesterol absorption efficiency of the intestine is inversely proportional to the rate of hepatic cholesterol biosynthesis.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…These results clearly demonstrated that the D19H polymorphism, even though it was rare, significantly contributed to an independent genetic risk of developing high total cholesterol and LDL-C levels. As reports have shown previously, this points to the fact that subjects with D19H/19H (GC or CC) variants are disposed to having a lower cholesterol absorption efficiency Hubáček et al 2004;Kajinami et al 2004aKajinami et al , 2004b. However, the cholesterol absorption efficiency of the intestine is inversely proportional to the rate of hepatic cholesterol biosynthesis.…”
Section: Discussionmentioning
confidence: 68%
“…However, subjects with D19H/19H variants were noted to exhibit greater reductions in LDL-C levels with statin treatment under the NCEP step 1 diet throughout the study. The greater response of LDL-C to statin treatment could be explained by a compensatory increase in endogenous cholesterol synthesis in subjects with D19H/19H variants compared to the D19 variant (Kajinami et al 2004a(Kajinami et al , 2004b. The discordance between our results for the serum total cholesterol and LDL-C levels in our subjects with D19H and previous results may be attributed to the following reasons: (1) the populations studied had different recruitment criteria for serum lipid levels; (2) dietary habits of different races; (3) different dietary interventions within the study period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 Indeed, there are published data about an association between the D19H variant and serum cholesterol levels. 26,27 Moreover, recent genome-wide studies identified an association of LDL cholesterol with proxies to D19H and the other ABCG8 variant rs4245791. 22,23 This effect could be confirmed in the present study (online-only Data Supplement Figure VI), albeit the association of D19H (and the other variants we identified) with serum cholesterol levels was only weak, and effects on phytosterols remained highly significant after normalization to cholesterol (Table) or adjustment to LDL cholesterol (online-only Data Supplement Table XVII).…”
Section: Discussionmentioning
confidence: 99%